2009
DOI: 10.1016/j.febslet.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

MCL‐1ES, a novel variant of MCL‐1, associates with MCL‐1L and induces mitochondrial cell death

Abstract: Edited by Barry Halliwell Keywords:Myeloid cell leukemia-1 MCL-1L MCL-1 extra short BCL-2 family Apoptosis Splicing variant a b s t r a c t Myeloid cell leukemia-1 (MCL-1L) is a pro-survival member of the BCL-2 family that promotes cell survival. In this study, we identify a new splicing variant of human MCL-1 that encodes MCL-1ES (extra short). Sequence analysis indicates that this variant results from splicing within the first coding exon of MCL-1 at a non-canonical GC-AG donor-acceptor pair. The deduced seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 16 publications
3
56
0
Order By: Relevance
“…In human, three splice variants of MCL-1 have been described, namely the anti-apoptotic isoform MCL-1L and the pro-apoptotic isoforms MCL-1S and MCL-1ES. At the post-translational level, caspase-mediated MCL-1 cleavage has also been observed [37, 38]. This supports our results that MCL-1 cleavage is caspase-mediated.…”
Section: Discussionsupporting
confidence: 91%
“…In human, three splice variants of MCL-1 have been described, namely the anti-apoptotic isoform MCL-1L and the pro-apoptotic isoforms MCL-1S and MCL-1ES. At the post-translational level, caspase-mediated MCL-1 cleavage has also been observed [37, 38]. This supports our results that MCL-1 cleavage is caspase-mediated.…”
Section: Discussionsupporting
confidence: 91%
“…2b). The probe for MCL-1L also detects MCL-1ES but the later is likely expressed at much lower levels than MCL-1L and MCL-1S as reported previously (Kim 2009; Kim and Bae 2013; Palve et al 2014). These data show the up-regulation of MCL-1/ES transcripts following transfection of miR-29b in intestinal fibroblasts.
Fig.
…”
Section: Resultssupporting
confidence: 68%
“…1b); MCL-1L is the full-length and most abundant isoform. MCL-1S is expressed at lower levels than MCL-1L (Bae et al 2000; Bingle et al 2000; Garzon et al 2009; Li et al 2013; Kim 2009; Kim and Bae 2013), whilst MCL-1ES was identified as minimally expressed by RT-PCR (Kim 2009). In cancer, MCL-1L was expressed at much higher levels than MCL-1S and MCL-1ES isoforms; the latter was expressed at low or undetectable levels (Palve et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Mcl-1 has been shown to contribute in resistance of cancer cells to chemotherapeutic agents, however reports on its role in radiation induced apoptosis and radioresistance are rare [12,13]. Further, the situation is complex due to the existence of distinct Mcl-1 isoforms having contrasting functions (anti-apoptotic Mcl-1L, pro-apoptotic Mcl-1S & Mcl-1ES)[14]. Earlier studies from our lab have demonstrated a five to ten fold higher expression of anti-apoptotic Mcl-1L transcript, versus the pro-apoptotic Mcl-1S in oral tumors [10].…”
Section: Introductionmentioning
confidence: 99%